Methodic of skills’ formation of light athletics motor actions with the help of inter-disciplinary communications and informational technologies, worked out for senior form pupils - Kozina, Zh.L.; Al-Ravashdeh, Abdel Baset; Kramskoy, S.I.; Ilnickaya, A.S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: to work out and substantiate technologies of motor and intellectual aspects’ integral influence on development of basic light athletics movements’ technique. Material: in the research 2 groups of schoolchildren participated: control group (n = 34) and experimental group (n = 33). Results: it was determined that main direction of motor skills’ development in light athletics trainings is a holistic approach. Such approach implies mastering of principal movements of light athletics on the base of analogies with rational and economical movements in Nature and on the base of laws of mechanics. Conclusions: it is recommended to consider in trainings the fact that improvement of motor skills’ mastering facilitates strengthening of demand in motor functioning. This demand is a condition of organism functioning’s improvement.